The Effect of Using the Geogebra Application on the Learning Outcomes of Applied Mathematics Courses at Merchant Marine Polytechnic of Makassar - Fauziah, Gradina Nur (Ridwan Institute, 2023)
GeoGebra is an application used to visualize mathematical concepts with the advantages of being easy to use, available in Indonesian, quite complete features in learning mathematics, and suitable for teaching tangent circle material. Therefore, the GeoGebra application makes it easier for students to visualize mathematical concepts on circle tangent material. The type of research used in this study is experimental research. Experimental research can be interpreted as a research method used to look for the effect of certain treatments on others under controlled conditions.